Comparative Thermal Analysis of Single and Double Channel Cold Plates for LiFePO4 Battery Modules - Yamin, Mohamad; Gufroni, Aldi (The Indonesian Institute of Science and Technology Research, 2026)
Li-ion batteries provide many advantages and are essential components of energy-storage systems for electric automobiles. A crucial aspect of battery operation is the maintenance of optimal temperature levels, which necessitate the implementation of a robust battery thermal management system. This study assessed the efficacy of two cold-plate configurations, a single parallel channel and a double parallel channel, in regulating the temperature of a 7 Ah LiFePO4 battery module comprising of three cells. Employing ANSYS 2023 R1 Academic License, a numerical analysis was performed to evaluate their performance. A battery discharge rate of 5C was used to investigate the changes in the mass flow rates ranging from 0.001 to 0.005 kg/s. The cooling fluid and ambient temperatures were maintained at 25°C. This study shows that double parallel-channel cold plates can be more effective than single parallel-channel cold plates in reducing battery module temperatures. Additionally, the use of double parallel-channel cold plates can result in a lower cooling fluid pressure drop. In addition, the cooling fluid used in the double parallel channel cold plate had a lower heat-transfer coefficient and Nusselt number.